A simulation study of slope stability affected by construction of new buildings at Universiti Teknologi Malaysia, Skudai. - Kassim, Azrnan; Kasim, Fauziah (Faculty of Civil Engineering, UTM, 2003)

(untitled)
Landslide occurrences had caused failure of sheet pile wall located about 6 m from Bangunan Tambahan, Fakulti Kejuruteraan Mekanikal (FKM), Universiti Telcnologi Malaysia in Skudai, Johor. With the aim of investigating cause(s) of the failure, the slope stability conditions prior and after construction were simulated using SLOPE/W Version 3.03. The results showed that effects of load of a newly filled water tank sited on the top of slope contributed to subsident of the slope surface within the vicinity by creating tension cracks near its raft footing. The slope became more unstable as the soil moisture or pore-water pressure increased due to infiltration of rainwater. This has reduced the shear strength, in particular the cohesion value, c. The simulation also confirmed the hyphothesis that the global soil mass movement started from the hill top where the water tank was located toward the installed sheet pile. The combined mobilized shear force and lateral pressure of the global slope was about 8 times the strength of the sheet pile. The associated stresses are found to be related to the formation of the heave pushing up the soil at the toe of slope and soil under the road pavement adjacent to the new laboratory buildings.